2015
DOI: 10.1111/hiv.12261
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in HIV infection: a prospective echocardiographic study

Abstract: Echocardiographic screening detected PH in a substantial proportion of HIV-positive patients. Female gender, a history of injecting drug use and HPC origin were associated with a higher prevalence of HIV-associated PH. The relevance and long-term outcome of these findings need to be validated in follow-up studies, which are ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 15 publications
4
40
1
2
Order By: Relevance
“…HIV‐associated PAH is a devastating and life‐threatening condition with recent cohort studies reporting prevalence ranging from 2.6% to 15.5% . Furthermore, a higher percentage of HIV‐infected individuals among intravenous drug users correlate with higher prevalence of HIV‐PAH in HIV‐infected patients . Our previous published findings also extensively highlight the exacerbated pulmonary vascular remodeling in the presence of both HIV‐viral proteins and drugs of abuse such as cocaine and morphine, therefore supporting the multiple‐hit hypothesis of PAH …”
Section: Introductionsupporting
confidence: 79%
“…HIV‐associated PAH is a devastating and life‐threatening condition with recent cohort studies reporting prevalence ranging from 2.6% to 15.5% . Furthermore, a higher percentage of HIV‐infected individuals among intravenous drug users correlate with higher prevalence of HIV‐PAH in HIV‐infected patients . Our previous published findings also extensively highlight the exacerbated pulmonary vascular remodeling in the presence of both HIV‐viral proteins and drugs of abuse such as cocaine and morphine, therefore supporting the multiple‐hit hypothesis of PAH …”
Section: Introductionsupporting
confidence: 79%
“…In the large prevalence study by Sitbon et al, PAH prevalence in HIV‐infected patients was found to be 0.46%. However, in many studies performed years after this study, the prevalence was detected to be 2.6%–6.1% . These findings indicated that HIV‐infected patients in the general population should be assessed for PAH development more carefully, and a screening strategy is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that HIV‐associated PAH prevalence is comparable with the prevalence in pre‐HAART era (0.46%) . Recent studies have shown that prevalence has increased to 2.6%–6.1% . Current pulmonary hypertension (PH) classification consists of five main groups .…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence is lower than COPD and symptoms of fatigue, dyspnea and cough may initially be absent (64). Echo-based screening may both over and under-diagnose PAH depending on sPAP cut-offs used (110, 111). These observations lead some to conclude screening asymptomatic HIV-seropositive patients for PAH should not be performed (69).…”
Section: Screening For Lung Disease In Hivmentioning
confidence: 99%
“…These observations lead some to conclude screening asymptomatic HIV-seropositive patients for PAH should not be performed (69). The invasiveness and availability of RHC limit its use as a screening tool; however, growth differentiation factor (GDF)-15 and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in serum are strongly associated with increased sPAP (63, 111), so could have potential as biomarkers in a screening protocol.…”
Section: Screening For Lung Disease In Hivmentioning
confidence: 99%